User centric community clouds - Barraca, João Paulo Silva (2011)
With the evolution in cloud technologies, users are becoming acquainted with seamless service provision. Nevertheless, clouds are not a user centric technology, and users become completely dependent on service providers. We propose a novel concept for clouds, where users self-organize to create their clouds. We present such an architecture for user-centric clouds, which relies on self-managed clouds based on doctrine and on identity management concepts.